Mode of Action of Antimicrobial Peptides on E. coli Spheroplasts - Sun, Yen (Biophys J, 2016)
We investigated the phenomena of antimicrobial peptides (AMPs) directly attacking the cytoplasmic membranes of Escherichia coli spheroplasts. We developed a procedure for fluorescence recovery after photobleaching to examine dye leakage through bacterial membranes as AMPs in solution bound to the membranes. We found that the AMP binding did not increase the apparent membrane area of a spheroplast, contrary to the response of a lipid-bilayer vesicle, which always showed a membrane area expansion by AMP binding. The permeability through the bacterial membrane increased in a sigmoidal fashion as the AMP binding increased in time, exhibiting a cooperative behavior of AMPs. The analysis of fluorescence recovery after photobleaching showed that the fluxes of dye molecules into and out of the cell were consistent with diffusion of molecules through a number of pores that increased with binding of AMPs and then saturated to a steady level. We discovered a new, to our knowledge, experimental parameter called the flux rate that characterizes the AMP-induced permeability of dye molecules through bacterial membranes. The phenomena observed in bacterial membranes are consistent with the pore-forming activities of AMPs previously observed in lipid bilayers. The experimental value of the flux rate per pore is much smaller than a theoretical value that assumes no friction for the dye molecule’s permeation through the pore. We believe that experimental studies of the flux rate will be useful for further analysis of AMPs’ permeabilization mechanisms.